Undergraduate Entrepreneurial Intentions and Personal Attitude Towards Entrepreneurship in Natural Product Chemistry - Worokwu, Chinda (Researchparks Publishing, 2025)
This study was carried out to determine the relationship between personal attitude and undergraduates’ entrepreneurial intentions towards entrepreneurship in natural product chemistry in Ignatius Ajuru University of Education Port Harcourt Rivers State, Nigeria. Correlation research design was adopted and the sample comprised 54 Final year undergraduate in Chemistry Education Undergraduates Department in Ignatius Ajuru University of Education, Rumuolumeni Port Harcourt, Nigeria. The instrument was a -17item questionnaire “tagged” Students’ Entrepreneurial Intentions Questionnaire (SEIQ) with reliability coefficient of 0.87 determined by Alpha Cronbach formula. Research questions were answered using mean and standard deviation and hypothesis tested at 0.05 level of significance. Findings of revealed a positive correlation between entrepreneurial intentions and personal attitude as well as behavioural control. High extent of science education undergraduates’ entrepreneurial intentions, attitude and entrepreneurial behavior of science education undergraduate towards entrepreneurship in natural product was obtained. It was recommended among others that natural products chemistry should be taught as a practical course to increase the entrepreneurial intention of students.